Effect of Exopolysaccharides on Phage-Host Interactions in Lactococcus lactis - Deveau, Hélène (American Society for Microbiology, 2002)
In this study, we report that Lactococcus lactis strains producing exopolysaccharides (EPS) are sensitive to virulent phages. Eight distinct lytic phages (Q61 to Q68) specifically infecting Eps(+) strains were isolated in 47 buttermilk samples obtained from 13 North American factories. The eight phages were classified within the 936 species by the multiplex PCR method, indicating that these phages are not fundamentally distinct from those infecting Eps(−) L. lactis strains. The host range of these phages was determined with 19 Lactococcus strains, including 7 Eps(+) and 12 Eps(−) cultures. Three phages (Q62, Q63, and Q64) attacked only the Eps(+) strain SMQ-419, whereas the five other phages (Q61, Q65, Q66, Q67, and Q68) infected only the Eps(+) strain SMQ-420. The five other Eps(+) strains (H414, MLT2, MLT3, SMQ-461, and SMQ-575) as well as the 12 Eps(−) strains were insensitive to these phages. The monosaccharide composition of the polymer produced by the seven Eps(+) strains was determined. The EPS produced by strains MLT3, SMQ-419, and SMQ-575 contained glucose, galactose, and rhamnose. The EPS fabricated by H414 contained only galactose. The EPS made by MLT2, SMQ-420, and SMQ-461 contained glucose and galactose. These findings indicate that the sugar composition of the EPS has no effect on phage sensitivity. The plasmid encoding the eps operon was cured from the two phage-sensitive strains. The cured derivatives were still phage sensitive, which indicates that EPS are not necessary for phage infection. Phage adsorption assays showed that the production of EPS does not confer a significant phage resistance phenotype.